Lessons from gefitinib-induced interstitial lung disease in Japan: Problems in approval, pharmacovigilance, and regulatory decision-making procedures - Tsutomu Nishimura (Pharmacy Practice, 2006)
Objective: The objective of this study was to identifyproblems in the approval, pharmacovigilance, andpost-approval regulatory decision-makingprocedures involving gefitinib and to proposecountermeasures to prevent further drug-inducedsuffering in Japan in the future.Methods: We comprehensively reviewed reportsregarding gefitinib published during the period from2000 to 2006 by regulatory agencies, themanufacturer of the gefitinib-containing drug, cancerclinical study groups, and a scientific society.Results: We identified the following major problemsin the approval, pharmacovigilance, and regulatorydecision-making procedures: 1) the results ofanimal experiments and pre-marketing clinical trials,and reports of adverse drug reactions from othercountries were not properly reflected in the label; 2)indications for the drug were expanded without strictevaluation of the external validity of pre-marketingclinical trials; and 3) despite many serious cases ofinterstitial lung disease (ILD) being spontaneouslyreported, well-designed post-marketing surveillancewas not immediately performed.Conclusions: We propose a mandatory total registryof all drug users and surveillance (i.e. a prospectiveoutcome study) as one of the rational solutions forpreventing further drug-induced suffering in Japan.